2011
DOI: 10.1183/09031936.00094910
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic nonspecific interstitial pneumonia: an interstitial lung disease associated with autoimmune disorders?

Abstract: Recent evidence suggests that idiopathic nonspecific interstitial pneumonia (iNSIP) is a distinct clinical entity amongst other idiopathic interstitial pneumonias, and some data seem to suggest a possible pathogenetic role of autoimmunity. The aim of the present study was to assess if iNSIP might represent an early lung manifestation of an autoimmune disease.After initial review of cases found in the medical records database by searching for the term ''NSIP'' (n563), 37 iNSIP cases were identified, and were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 33 publications
8
79
1
3
Order By: Relevance
“…This is consistent with several studies that show a clear link between NSIP histology and CTD [9,42,43]. Two recent studies have demonstrated that 10% and 52% of their patients who were considered to have idiopathic NSIP developed CTD during the follow-up period [43,44]. In another study, a close association between NSIP histology and UCTD was demonstrated: NSIP was the histological diagnosis in 15 out of 17 patients with UCTD (OR 50; p50.0001), leading the authors to surmise that the application of diagnostic criteria for UCTD may identify NSIP before obtaining surgical lung biopsy [9].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with several studies that show a clear link between NSIP histology and CTD [9,42,43]. Two recent studies have demonstrated that 10% and 52% of their patients who were considered to have idiopathic NSIP developed CTD during the follow-up period [43,44]. In another study, a close association between NSIP histology and UCTD was demonstrated: NSIP was the histological diagnosis in 15 out of 17 patients with UCTD (OR 50; p50.0001), leading the authors to surmise that the application of diagnostic criteria for UCTD may identify NSIP before obtaining surgical lung biopsy [9].…”
Section: Discussionsupporting
confidence: 80%
“…This is consistent with several studies that show a clear link between NSIP histology and CTD [9,42,43]. Two recent studies have demonstrated that 10% and 52% of their patients who were considered to have idiopathic NSIP developed CTD during the follow-up period [43,44].…”
Section: Discussionsupporting
confidence: 77%
“…As in previous studies, our patients with UCTD were more likely to be females [5,8,30] and nonsmokers [5,30] than those with idiopathic NSIP. UCTD patients were similar to CTDs patients, including in terms of demographic characteristics and survival.…”
Section: Discussionsupporting
confidence: 56%
“…Indeed, the pathologic pattern observed in CTD does not seem to affect the prognosis and survival as clearly as in the idiopathic setting. Although patients with idiopathic NSIP [20] or idiopathic desquamative interstitial pneumonia [21] have a dramatically better long-term survival than those with IPF [22][23][24], such a difference was not found in patients with systemic sclerosis or rheumatoid arthritis [3,10]. Studies correlating the pathological pattern with outcome all suffer the limitation of a high risk of constitutive selection bias, with lung biopsy being performed in individuals with the least typical pattern of disease at imaging.…”
Section: Does the Diagnosis Of Established Ctd Affect Prognosis Or Mamentioning
confidence: 99%
“…In one series of ILD associated with anti-synthetase antibodies, respiratory manifestations occurred before the onset of muscle or skin disease in 55% of the patients [32]. Long-term follow-up of patients with NSIP may lead to the subsequent diagnosis of CTD in a significant proportion of patients [20,33,34], suggesting that subtle extra-thoracic features of systemic disease present at baseline might have been overlooked. Identification of the CTD may be difficult when the onset of disease is acute or subacute, as often observed in inflammatory idiopathic myopathy (especially associated with anti-melanoma differentiation associated gene (MDA5) antibodies) [35].…”
Section: Ctd Features May Be Missed In the Diagnostic Approach Of Ildmentioning
confidence: 99%